How Does a Young Adult with Autism Respond to Directive Speech Acts conveyed in a Podcast? - Hadiyani, Teni; Sudana, Dadang; Fatimah, Siti; Kurnihayati, Kurnihayati (SCOPE: Journal of English Language Teaching, 2024)
Autistic Spectrum Disorder is a mental development disorder that can affect the ability to communicate and behave. This study has an aim to find out what kind of DSA uttered by the host DC and how a young adult Youtuber with Autistic Spectrum Disorder (ASD) responds to speech acts focused on directive speech acts. The method of this research was descriptive qualitative. The data were collected from the conversation between DC and NF, a Youtuber with ASD in the 'Close the Door' podcast on his YouTube channel in 2021. From the results of data analysis, it can be seen that DC uttered questions mostly among other DSA types initiated by Allan (1986), the type that appears the most was questions, it appears 52 times during 16 minutes and 17 seconds conversation with various responses, with actions, one- or two-word answers, repetition, and unrelated long answers.